PENGARUH FAKTOR TEKNOLOGI, ORGANISASI, DAN LINGKUNGAN TERHADAP PERFORMA PERUSAHAAN PADA IMPLEMENTASI SISTEM SERIALISASI DI PT BIO FARMA (PERSERO) - Maeka, Lita; Usman, Osly; Budiantoro, Anandha (Journal of Management and Leadership, 2024)
A serialization system is a technological solution that enables product tracking and traceability by providing a unique identity for each product unit. This system can prevent the circulation of counterfeit products in the supply chain of pharmaceutical products. Companies must deploy this serialization system technology to comply with applicable requirements and maintain competitiveness. This study aims to determine the effect of TOE framework on the implementation of the serialization system on company performance using a survey/questionnaire method at PT Bio Farma (Persero). Statistical testing uses Structured Equation Modeling (SEM) to measure the relationship between variables. The test result identified that technological, organizational, and environmental contexts have a positive and significant impact on the serialization system's implementation at Bio Farma. The results also revealed that the implementation of the serialization system has had a positive and significant impact on company performance. This research can have good implications for companies and top management in providing appropriate and compatible technology support so that the adoption of implementation serialization technology can improve company performance.